Integrated Care for Older Adults: A Struggle for Sustained Implementation in Northern Netherlands - Holterman, Sander; Lahr, Maarten; Wynia, Klaske; Hettinga, Marike; Buskens, Erik (International journal of integrated care, 2020)
Integrated care has been suggested as a promising solution to the disparities in access and sustained high quality long-term care emerging in Europe's ageing population. We aim to gain a better understanding of context-specific barriers to and facilitators of implementation of integrated care by doing a retrospective assessment of seven years of Embrace. This Dutch integrated person-centred health service for older adults was based on two evidence-based models (the Chronic Care Model and the Kaiser Permanente Triangle). Despite successful deployment the programme ended in 2018. In this case study we assess the impact of the programme based on past evaluations, reflect on why it ended, lessons learned and ideas to take forward. The majority of health outcomes were positive and the perceived quality of care improved, albeit no clear-cut savings were observed, and the costs were not balanced across stakeholders. The Embrace payment model did not support the integration of health services, despite reforms in long-term care in 2015. Enabling policy and funding are crucial to the sustained implementation of integrated person-centred health services. The payment model should incentivize the integration of care before the necessary changes can be made at organizational and clinical levels towards providing proactive and preventive health services.